Direct trifluoromethylation of imidazoheterocycles in a recyclable medium at room temperature. Issue 38 (27th March 2015) - Ji, Xiao-Ming; Wei, Liang; Chen, Fan; Tang, Ri-Yuan
Abstract : Regioselective C–H trifluoromethylation of imidazoheterocycles with Langlois' reagent in a recyclable mixed medium of 1-butyl-3-methylimidazoliumtetrafluoroborate ([Bmim]BF4 ) and water at room temperature has been developed. Abstract : Regioselective C–H trifluoromethylation of imidazoheterocycles with Langlois' reagent in a recyclable mixed medium of 1-butyl-3-methylimidazoliumtetrafluoroborate ([Bmim]BF4 ) and water at room temperature has been developed. In the presence of catalytic cupric acetate and 2-methyl-2-(methylperoxy)propane (TBHP), this green strategy tolerates a wide range of functional groups to afford diverse trifluoromethylated imidazoheterocycles in moderate to good yields.